Liquid Structure and Dynamics in the Choline Acetate:Urea 1:2 Deep Eutectic Solvent - Triolo, A.; Pietro, M. E. Di; Mele, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Martinelli, A.; Chater, P.; Russina, O. (J. Chem. Phys.)

Switching Between Proton Vacancy and Excess Proton Transfer Pathways in the Reaction Between 7-Hydroxyquinoline and Formate - Codescu, M.-A.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. A)

Efficient EOM-CC-Based Protocol for the Calculation of Electron Affinity of Solvated Nucleobases: Uracil as a Case Study - Mukherjee, M.; Tripathi, D.; Brehm, Martin; Riplinger, C.; Dutta, A. K. (J. Chem. Theory Comput.)

Liquid Structure of a Choline Chloride-Water Natural Deep Eutectic Solvent: A Molecular Dynamics Characterization - Triolo, A.; Celso, F. Lo; Brehm, Martin; Lisio, V. Di; Russina, O. (J. Mol. Liq.)

Qualität sozialer Interaktionen von Jugendlichen mit emotionalen Problemen oder Problemen im Umgang mit Peers im Unterricht – Eine Pilotstudie mit der Experience Sampling Method - Knickenberg, Margarita; Zurbriggen, C.

Gender, special education needs, and inclusion: Evidence from the Perceptopions of Inclusion Questionnaire in Sweden - DeVries, J. M.; Knickenberg, Margarita; Trygger, M.

Academic self-concept, perceptions of inclusion, special needs and gender: Evidence from inclusive classes in Sweden - DeVries, Jeffrey M.; Knickenberg, Margarita; Trygger, Maria (European Journal of Special Needs Education)
Keywords: Developmental and Educational Psychology; Health Professions (miscellaneous); Education

Reintroduction of Running After Anterior Cruciate Ligament Reconstruction With a Hamstrings Graft: Can We Predict Short-Term Success? - Pairot de Fontenay, Benoit; Van Cant, Joachim; Gokeler, Alli; Roy, Jean-Sébastien (Journal of Athletic Training)
Context Return to running (RTR) after anterior cruciate ligament reconstruction (ACLR) is a crucial milestone. However, how and when to start a running program are uncertain. Objective To explore the feasibility of a structured program to reintroduce running after ACLR and evaluate the predictive value of potential predictors of short-term success. Design Longitudinal cohort study. Setting Local research center and participants' homes. Patients or Other Participants Thirty-five participants were recruited after ACLR. Intervention(s) Program with a progression algorithm to reintroduce running (10 running sessions in 14 days). Main Outcome Measure(s) The criterion for short-term success was no exacerbation of symptoms. Potential predictors were (1) the International Knee Documentation Committee (IKDC) subjective knee form score, (2) ACL Return to Sport after Injury questionnaire score, (3) quadriceps and hamstrings strength, (4) step-down endurance test, and (5) modified Star Excursion Balance test. Descriptive statistics were performed to study the feasibility of the RTR program, and Poisson regression analysis was used to evaluate predictors of success. Results Of the 34 participants, 33 completed the RTR program. Sixteen participants experienced some temporary exacerbation of symptoms, but only 1 had to stop the program. The initial IKDC score was the only significant predictor of a successful RTR, with an area under the receiver operating characteristic curve of 80.4%. An IKDC cut-off of 63.7/100 differentiated responders and nonresponders with the highest sensitivity and specificity (77.8% and 75.0%, respectively). A participant with an IKDC score above this threshold had a 3-fold greater chance of success. Conclusions Our results confirm the feasibility of our RTR program and progression algorithm after ACLR. Clinicians should use an IKDC score of >64 as a criterion to reintroduce running after ACLR to increase the likelihood of short-term success.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

An Exploratory Meta-Analytic Review on the Empirical Evidence of Differential Learning as an Enhanced Motor Learning Method - Tassignon, Bruno; Verschueren, Jo; Baeyens, Jean-Pierre; Benjaminse, Anne; Gokeler, Alli; Serrien, Ben; Clijsen, Ron (Frontiers in Psychology)
Background: Differential learning (DL) is a motor learning method characterized by high amounts of variability during practice and is claimed to provide the learner with a higher learning rate than other methods. However, some controversy surrounds DL theory, and to date, no overview exists that compares the effects of DL to other motor learning methods. Objective: To evaluate the effectiveness of DL in comparison to other motor learning methods in the acquisition and retention phase. Design: Systematic review and exploratory meta-analysis. Methods: PubMed (MEDLINE), Web of Science, and Google Scholar were searched until February 3, 2020. To be included, (1) studies had to be experiments where the DL group was compared to a control group engaged in a different motor learning method (lack of practice was not eligible), (2) studies had to describe the effects on one or more measures of performance in a skill or movement task, and (3) the study report had to be published as a full paper in a journal or as a book chapter. Results: Twenty-seven studies encompassing 31 experiments were included. Overall heterogeneity for the acquisition phase (post-pre; I 2 = 77%) as well as for the retention phase (retention-pre; I 2 = 79%) was large, and risk of bias was high. The meta-analysis showed an overall small effect size of 0.26 [0.10, 0.42] in the acquisition phase for participants in the DL group compared to other motor learning methods. In the retention phase, an overall medium effect size of 0.61 [0.30, 0.91] was observed for participants in the DL group compared to other motor learning methods. Discussion/Conclusion: Given the large amount of heterogeneity, limited number of studies, low sample sizes, low statistical power, possible publication bias, and high risk of bias in general, inferences about the effectiveness of DL would be premature. Even though DL shows potential to result in greater average improvements between pre- and post/retention test compared to non-variability-based motor learning methods, more high-quality research is needed before issuing such a statement. For robust comparisons on the relative effectiveness of DL to different variability-based motor learning methods, scarce and inconclusive evidence was found.
Keywords: General Psychology

Effective Attentional Focus Strategies after Anterior Cruciate Ligament Reconstruction: A Commentary - Singh, Harjiv; Gokeler, Alli; Benjaminse, Anne (International Journal of Sports Physical Therapy)
Individuals after anterior cruciate ligament reconstruction (ACLR) have a high rate of reinjury upon return to competitive sports. Deficits in motor control may influence reinjury risk and can be addressed during rehabilitation with motor learning strategies. When instructing patients in performing motor tasks after ACLR, an external focus of attention directed to the intended movement effect has been shown to be more effective in reducing reinjury risk than an internal focus of attention on body movements. While this concept is mostly agreed upon, recent literature has made it clear that the interpretation and implementation of an external focus of attention within ACLR rehabilitation needs to be better described. The purpose of this commentary is to provide a clinical framework for the application of attentional focus strategies and guide clinicians towards effectively utilizing an external focus of attention in rehabilitation after ACLR. Level of Evidence 5
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation

Rehabilitation strategies of Flemish physical therapists before and after anterior cruciate ligament reconstruction: An online survey - Dingenen, Bart; Billiet, Bart; De Baets, Liesbet; Bellemans, Johan; Truijen, Jan; Gokeler, Alli (Physical Therapy in Sport)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Die Aufteilung der Barentsseegebiete mithilfe des Adjusted Winner Verfahrens bei asymmetrischen Machtverhältnissen - N., N.

Versionisierung von Serviceleistungen auf Videoplattformen - N., N.

Kindergarten Allocation through Matching Mechanisms - N., N.

Faire Profitverteilung in Energienetzwerken - eine spieltheoretische Analyse von Microgrids - N., N.

"First-Party-Content" auf zweiseitigen Märkten - N., N.

Stability in many-to-many matchings with contracts - N., N.

Preissetzungsstrategien für Neuprodukte - N., N.

Co-opetition in Two-Sided Markets - N., N.

Matching mit Minderheiten - N., N.

Piracy and Visioning - N., N.

Revenue Sharing Contracts: Horizontale Koordination in der E-Commerce-Logistik - N., N.

Design and Implementation of a Crowd-based Prototype Validation Platform - N., N.

Model-based Continuous Experimentation for Software Product Prototypes - N., N.

Lightweight Process Engine for Situation-specific Development of Business Models for Digital Platforms - N., N.

Development and Evaluation of a Multi Platform Approach for Augmented Reality Product Configuration - N., N.

Model-based Feature Backlog Synchronization for Dual-Track Development Methods - N., N.

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.

Device-Independent Security Proofs Via Entropy Accumulation - Anonymous, Anonymous

David und Salomo im Koran: ein Komparativ-theologischer Ansatz - Saad, Nadia (Methoden der Darstellung und Analyse interreligiöser Diskurse)

Reading Iqbal in the Light of Kierkegaard; towards an Existentialist Approach to Islam - Mir Sadri, Seyedeh Saeideh; Nasiri, Mansour (Philosophy East and West)

Fratelli e sorelle tutti. Die Sozialenzyklika aus islamischer Sicht - Mir Sadri, Seyedeh Saeideh (Amos-international)

"Ein altes Familientalent" - Kinderzeichnungen aus der Familie der Brüder Grimm (1. Hälfte 19. Jh.) in der Grimm-Sammlung der Stadt Kassel. Germany - Eikermann, Larissa (Das Erbe der Kinder: Provenienzforschung und Sammlungsgeschichte von Kinder- und Jugendzeichnungen: Museen, Archive, private Kollektionen und "verschwundene Sammlungen" = The children's heritage: provenance research and the history of children's and youth drawings collections: museums, archives, private holdings and "lost collections")

Children´s drawings on Pippi & Co. - A visit to the Astrid Lindgren Archive in the Royal Library of Stockholm. Sweden - Eikermann, Larissa (Das Erbe der Kinder: Provenienzforschung und Sammlungsgeschichte von Kinder- und Jugendzeichnungen: Museen, Archive, private Kollektionen und "verschwundene Sammlungen" = The children's heritage: provenance research and the history of children's and youth drawings collections: museums, archives, private holdings and "lost collections")

Begegnungslernen in den Kerncurricula des islamischen Religionsunterrichts - Kamcili-Yildiz, Naciye (Interreligiöse Öffnung durch Begegnung. Grundlagen - Erfahrungen - Perspektiven im Kontext des christlich-islamischen Dialogs)

Zwischen Glaubensvermittlung und Reflexivität: Eine quantitative Studie zu professionellen Kompetenzen von islamischen ReligionslehrerInnen - Kamcili-Yildiz, Naciye

Supernatural, Unnatural, Queer: Gratitude and Nature in Islamic Political Theology - Mustafa, Abdul Rahman (Political Theology)

Carbon Dating of Seven Parchment Qurʾān Manuscripts and One Syriac Bible of the National Museum of Iran - Aghaei Abrandabadi, Seyed Ali; Marx, Michel (Journal of Iranian National Museum)

Kontrafaktische Intertextualität im Koran und die exegetische Tradition des syrischen Christentums - Ghaffar, Zishan (Der Islam)

Islamische systematische Theologie in Deutschland: Konturen eines jungen Faches - Tatari, Muna (Islamische Theologie in Deutschland. Ein Modell für Europa und die Welt)

Prophetin - Jungfrau - Mutter: Maria im Koran - Tatari, Muna; von Stosch, Klaus

Die unerwünschte Empfehlung, Hybris: Woran der Westen in Afghanistan tatsächlich gescheitert ist - Nassery, Idris (Frankfurter Allgemeine Zeitung)

Exploring the impact of pre-service science teachers’ reflection skills on the development of professional knowledge during a field experience - Kulgemeyer, Christoph; Kempin, Maren; Weißbach, Anna; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (International Journal of Science Education)
Keywords: Education

Erwerb und Messung physikdidaktischer Kompetenzen zum Einsatz digitaler Medien - Große-Heilmann, Rike Isabel; Burde, Jan-Philipp; Riese, Josef; Schubatzky, Thomas; Weiler, David (PhyDid B-Didaktik der Physik-Beiträge zur DPG-Frühjahrstagung 2021)

Entwicklung eines Seminars zur Förderung des Konzeptverständnisses mittels digitaler Medien - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (PhyDid B-Didaktik der Physik-Beiträge zur DPG-Frühjahrstagung 2021)

The Scope of ‘iṣma and Qur’anic Evidence - Haghani Fazl, Mohammad (Impeccability and Temptation: Understanding Christ's Divine and Human Will)

Additively processed TiAl6Nb7 alloy for biomedical applications - Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Correlation between pre- and post-treatments of additively manufactured 316L parts and the resulting low cycle fatigue behavior - Garthe, Kai-Uwe; Hoyer, Kay-Peter; Hagen, Leif; Tillmann, Wolfgang; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The currently existing restrictions regarding the deployment of additively manufactured components because of poor surface roughness, porosity and residual stresses as well as their influence on the low-cycle fatigue (LCF) strength are addressed in this paper. Design/methodology/approach This study aims to evaluating the effect of different pre- and post-treatments on the LCF strength of additively manufactured 316L parts. Therefore, 316L specimens manufactured by laser powder bed fusion were examined in their as-built state as well as after grinding, or coating with regard to the surface roughness, residual stresses and LCF strength. To differentiate between topographical effects and residual stress-related phenomena, stress-relieved 316L specimens served as a reference throughout the investigations. To enable an alumina coating of the 316L components, atmospheric plasma spraying was used, and the near-surface residual stresses and the surface roughness are measured and investigated. Findings The results have shown that the applied pre- and post-treatments such as stress-relief heat treatment, grinding and alumina coating have each led to an increase in LCF strength of the 316L specimens. In contrast, the non-heat-treated specimens predominantly exhibited coating delamination. Originality/value To the best of the authors’ knowledge, this is the first study of the correlation between the LCF behavior of additively manufactured uncoated 316L specimens in comparison with additively manufactured 316L specimens with an alumina coating.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Requirements for Processing High-Strength AlZnMgCu Alloys with PBF-LB/M to Achieve Crack-Free and Dense Parts - Heiland, Steffen; Milkereit, Benjamin; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Kessler, Olaf; Schaper, Mirko (Materials)
Processing aluminum alloys employing powder bed fusion of metals (PBF-LB/M) is becoming more attractive for the industry, especially if lightweight applications are needed. Unfortunately, high-strength aluminum alloys such as AA7075 are prone to hot cracking during PBF-LB/M, as well as welding. Both a large solidification range promoted by the alloying elements zinc and copper and a high thermal gradient accompanied with the manufacturing process conditions lead to or favor hot cracking. In the present study, a simple method for modifying the powder surface with titanium carbide nanoparticles (NPs) as a nucleating agent is aimed. The effect on the microstructure with different amounts of the nucleating agent is shown. For the aluminum alloy 7075 with 2.5 ma% titanium carbide nanoparticles, manufactured via PBF-LB/M, crack-free samples with a refined microstructure having no discernible melt pool boundaries and columnar grains are observed. After using a two-step ageing heat treatment, ultimate tensile strengths up to 465 MPa and an 8.9% elongation at break are achieved. Furthermore, it is demonstrated that not all nanoparticles used remain in the melt pool during PBF-LB/M.
Keywords: General Materials Science

Bioresorbable AgCe and AgCeLa alloys for adapted Fe-based implants - Krüger, Jan Tobias; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Implants often overtake body function just for a certain time and remain as an unnecessary foreign body or have to be removed. Thus, resorbable implants are highly beneficial to reduce patient burden. Besides established materials, Iron-(Fe)-based alloys are in focus due to superior mechanical properties and good biocompatibility. However, their degradation rate needs to be increased. Phases with high electrochemical potential could promote the dissolution of residual material based on the galvanic coupling. Silver (Ag) is promising due to its high electrochemical potential (+0.8 V vs. SHE), immiscibility with Fe, biocompatibility, and anti-bacterial properties. But to prevent adverse consequences the Ag-particles, remaining after dissolution of the matrix, need to dissolve. Thus, a bioresorbable Ag-alloy is required. Regarding the electrochemical potential and degradation behavior of binary alloys, Cerium (Ce) and Lanthanum (La) are well-suited considering their biocompatibility and antibacterial behavior. Accordingly, this research addresses AgCe and AgCeLa alloys as additives for Fe-based materials with adapted degradation behavior. Furthermore, degradable Ag-alloys combined with inert implant materials could enable the controlled release of antibacterial active Ag-ions.

Tribo-mechanical properties and biocompatibility of Ag-containing amorphous carbon films deposited onto Ti6Al4V - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Franke, Carlo; Kokalj, David; Stangier, Dominic; Filor, Viviane; Mateus-Vargas, Rafael Hernán; Oltmanns, Hilke; Kietzmann, Manfred; Meißner, Jessica; Hein, Maxwell; Pramanik, Sudipta; et al. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Laser beam melting of functionally graded materials with application-adapted tailoring of magnetic and mechanical performance - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Quasi in-situ analysis of fracture path during cyclic loading of double-edged U notched additively manufactured FeCo alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (International Journal of Fatigue)
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; Modeling and Simulation

Bioresorbable AgCe and AgCeLa alloys for adapted Fe-based implants - Krüger, Jan Tobias; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Soft-magnetic behavior of laser beam melted FeSi3 alloy with graded cross-section - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Haase, Michael; Gierse, Jan; Zimmer, Detmar; Tröster, Thomas; Schaper, Mirko (Journal of Materials Processing Technology)

Correlation between Taylor Model Prediction and Transmission Electron Microscopy-Based Microstructural Investigations of Quasi-In Situ Tensile Deformation of Additively Manufactured FeCo Alloy - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)
Abstract Within this research, the multiscale microstructural evolution before and after the tensile test of a FeCo alloy is addressed. X-ray µ -computer tomography (CT), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM) are employed to determine the microstructure on different length scales. Microstructural evolution is studied by performing EBSD of the same area before and after the tensile test. As a result, $$\langle$$ ⟨ 001 $$\rangle$$ ⟩ ||TD, $$\langle$$ ⟨ 011 $$\rangle$$ ⟩ ||TD are hard orientations and $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ ||TD is soft orientations for deformation accommodation. It is not possible to predict the deformation of a single grain with the Taylor model. However, the Taylor model accurately predicts the orientation of all grains after deformation. {123} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the most active slip system, and {112} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the least active slip system. Both EBSD micrographs show grain subdivision after tensile testing. TEM images show the formation of dislocation cells. Correlative HRTEM images show unresolved lattice fringes at dislocation cell boundaries, whereas resolved lattice fringes are observed at dislocation cell interior. Since Schmid’s law is unable to predict the deformation behavior of grains, the boundary slip transmission accurately predicts the grain deformation behavior.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Tribo-mechanical properties and biocompatibility of Ag-containing amorphous carbon films deposited onto Ti6Al4V - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Franke, Carlo; Kokalj, David; Stangier, Dominic; Filor, Viviane; Mateus-Vargas, Rafael Hernán; Oltmanns, Hilke; Kietzmann, Manfred; Meißner, Jessica; Hein, Maxwell; Pramanik, Sudipta; et al. (Surface and Coatings Technology)
The addition of Ag to amorphous carbon (a-C) films is highly effective in tailoring the tribo-mechanical properties and biocompatibility. For biomedical applications, Ag-containing a-C (a-C:Ag) represents a promising film material for improving the biofunctional surface properties of Ti-based alloys. In a sputtering process, a-C:Ag films, with Ag contents up to 7.5 at.%, were deposited with a chemically graded TixCy interlayer onto Ti6Al4V. The tribo-mechanical and biocompatible properties of a-C:Ag were evaluated. The influence of the Ag content on these properties was analyzed and compared to those of uncoated Ti6Al4V. Raman spectroscopy reveals that the amount of incorporated Ag does not induce significant structural changes in the disordered network, only a reduced number of vacancies and sp3-coordinated C bonds within the sp2-dominant a-C network is assigned to the films with high Ag concentration. With increasing Ag content, stresses, hardness, and elastic modulus decrease from (2.02 ± 0.07) to (1.15 ± 0.03) GPa, from (17.4 ± 1.5) to (13.4 ± 0.9) GPa, and from (171.8 ± 8.1) to (138.5 ± 5.8) GPa, respectively. In tribometer tests, the friction behavior against Al2O3 in lubricated condition with a simulated-body-fluid-based lubricant is not affected by the Ag concentration, but the Al2O3 counterpart wear is reduced for all a-C:Ag films compared to a-C. The friction against ultra-high-molecular-weight polyethylene (UHMWPE) decreases continuously with increasing Ag concentration and the counterpart wear is lower at higher Ag contents. Compared to a-C:Ag, Ti6Al4V demonstrates lower friction against UHMWPE and higher friction against Al2O3. The a-C:Ag films are not exposed to abrasion by Al2O3 or pronounced material transfer of UHMWPE. The hardness difference and chemical affinity between the friction partners are decisive for the tribological behavior of a-C:Ag. Compared to Ti6Al4V, the a-C:Ag films show antibacterial activity against Staphylococcus aureus, while the proliferation of osteoblast-like cells is reduced by Ag.

Intermetallic Phases Identification and Diffusion Simulation in Twin-Roll Cast Al-Fe Clad Sheet - Křivská, Barbora; Šlapáková, Michaela; Veselý, Jozef; Kihoulou, Martin; Fekete, Klaudia; Minárik, Peter; Králík, Rostislav; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Materials)
Aluminium steel clad materials have high potential for industrial applications. Their mechanical properties are governed by an intermetallic layer, which forms upon heat treatment at the Al-Fe interface. Transmission electron microscopy was employed to identify the phases present at the interface by selective area electron diffraction and energy dispersive spectroscopy. Three phases were identified: orthorhombic Al5Fe2, monoclinic Al13Fe4 and cubic Al19Fe4MnSi2. An effective interdiffusion coefficient dependent on concentration was determined according to the Boltzmann–Matano method. The highest value of the interdiffusion coefficient was reached at the composition of the intermetallic phases. Afterwards, the process of diffusion considering the evaluated interdiffusion coefficient was simulated using the finite element method. Results of the simulations revealed that growth of the intermetallic phases proceeds preferentially in the direction of aluminium.
Keywords: General Materials Science

Additively processed TiAl6Nb7 alloy for biomedical applications - Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Laser beam melting (LBM) is an advanced manufacturing technology providing special features and the possibility to produce complex and individual parts directly from a CAD model. TiAl6V4 is the most common used titanium alloy particularly in biomedical applications. TiAl6Nb7 shows promising improvements especially regarding biocompatible properties due to the substitution of the hazardous vanadium. This work focuses on the examination of laser beam melted TiAl6Nb7. For microstructural investigation scanning electron microscopy including energydispersive x-ray spectroscopy as well as electron backscatter diffraction are utilized. The laser beam melted related acicular microstructure as well as the corresponding mechanical properties, which are determined by hardness measurements and tensile tests, are investigated. The laser beam melted alloy meets, except of breaking elongation A, the mechanical demands like ultimate tensile strength Rm, yield strength Rp0.2, Vickers hardness HV of international standard ISO 5832-11. Next steps contain comparison between TiAl6Nb7 and TiAl6V4 in different conditions. Further investigations aim at improving mechanical properties of TiAl6Nb7 by heat treatments and assessment of their influence on the microstructure as well as examination regarding the corrosive behavior in human bodylike conditions.
Keywords: Laser beam melting; titanium alloy; TiAl6Nb7; biomedical engineering; implants

High Temperature Annealing of Twin-Roll Cast Al-Li-Based Alloy Studied by In-situ SEM and STEM - Cieslar, Miroslav; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Belejová, Sára; Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Microscopy and Microanalysis)
Keywords: Instrumentation

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Keywords: Materials Chemistry; Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Intermetallic Phase Growth in Al-steel Clad Strip during In-situ Heating in TEM - Křivská, Barbora; Šlapáková, Michaela; Minárik, Peter; Fekete, Klaudia; Králík, Rostislav; Stolbchenko, Mykhailo; Schaper, Mirko; Grydin, Olexandr (Microscopy and Microanalysis)
Keywords: Instrumentation

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)
Keywords: Industrial and Manufacturing Engineering; Engineering (miscellaneous); General Materials Science; Biomedical Engineering

Strength enhancement of AlMg sheet metal parts by rapid heating and subsequent cold die stamping of severely cold-rolled blanks - Camberg, Alan Adam; Andreiev, Anatolii; Pramanik, Sudipta; Hoyer, Kay-Peter; Tröster, Thomas; Schaper, Mirko (Materials Science and Engineering: A)

Correlation between Taylor Model Prediction and Transmission Electron Microscopy-Based Microstructural Investigations of Quasi-In Situ Tensile Deformation of Additively Manufactured FeCo Alloy - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)
Abstract Within this research, the multiscale microstructural evolution before and after the tensile test of a FeCo alloy is addressed. X-ray µ -computer tomography (CT), electron backscattered diffraction (EBSD), and transmission electron microscopy (TEM) are employed to determine the microstructure on different length scales. Microstructural evolution is studied by performing EBSD of the same area before and after the tensile test. As a result, $$\langle$$ ⟨ 001 $$\rangle$$ ⟩ ||TD, $$\langle$$ ⟨ 011 $$\rangle$$ ⟩ ||TD are hard orientations and $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ ||TD is soft orientations for deformation accommodation. It is not possible to predict the deformation of a single grain with the Taylor model. However, the Taylor model accurately predicts the orientation of all grains after deformation. {123} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the most active slip system, and {112} $$\langle$$ ⟨ 111 $$\rangle$$ ⟩ is the least active slip system. Both EBSD micrographs show grain subdivision after tensile testing. TEM images show the formation of dislocation cells. Correlative HRTEM images show unresolved lattice fringes at dislocation cell boundaries, whereas resolved lattice fringes are observed at dislocation cell interior. Since Schmid’s law is unable to predict the deformation behavior of grains, the boundary slip transmission accurately predicts the grain deformation behavior.

Correlation between pre- and post-treatments of additively manufactured 316L parts and the resulting low cycle fatigue behavior - Garthe, Kai-Uwe; Hoyer, Kay-Peter; Hagen, Leif; Tillmann, Wolfgang; Schaper, Mirko (Rapid Prototyping Journal)
Purpose The currently existing restrictions regarding the deployment of additively manufactured components because of poor surface roughness, porosity and residual stresses as well as their influence on the low-cycle fatigue (LCF) strength are addressed in this paper. Design/methodology/approach This study aims to evaluating the effect of different pre- and post-treatments on the LCF strength of additively manufactured 316L parts. Therefore, 316L specimens manufactured by laser powder bed fusion were examined in their as-built state as well as after grinding, or coating with regard to the surface roughness, residual stresses and LCF strength. To differentiate between topographical effects and residual stress-related phenomena, stress-relieved 316L specimens served as a reference throughout the investigations. To enable an alumina coating of the 316L components, atmospheric plasma spraying was used, and the near-surface residual stresses and the surface roughness are measured and investigated. Findings The results have shown that the applied pre- and post-treatments such as stress-relief heat treatment, grinding and alumina coating have each led to an increase in LCF strength of the 316L specimens. In contrast, the non-heat-treated specimens predominantly exhibited coating delamination. Originality/value To the best of the authors’ knowledge, this is the first study of the correlation between the LCF behavior of additively manufactured uncoated 316L specimens in comparison with additively manufactured 316L specimens with an alumina coating.

Novel AgCa and AgCaLa alloys for Fe-based bioresorbable implants with adapted degradation - Krüger, Jan Tobias; Hoyer, Kay-Peter; Filor, Viviane; Pramanik, Sudipta; Kietzmann, Manfred; Meißner, Jessica; Schaper, Mirko (Journal of Alloys and Compounds)
Resorbable implants are highly beneficial to reduce patient burden since they need not be removed after a defined period. Currently, magnesium (Mg) and polymers are being applied as bioresorbable materials. However, for some applications the insufficient mechanical properties and high degradation rate of Mg cause the need for new materials. Iron (Fe)-based alloys are promising due to their biocompatibility and good mechanical properties, but their degradation rate is too low and needs to be adapted eg. via alloying with manganese (Mn). Besides, phases with high electrochemical potential lead to increased degradation of residual material with lower potential based on the galvanic coupling. Here, silver (Ag) is promising for the formation of such phases due to its high electrochemical potential (+0.8 V vs. SHE), immiscibility with Fe, biocompatibility, and anti-bacterial properties. Since remaining silver particles can lead to adverse consequences as thrombosis, these particles need to dissolve after the matrix material. Thus a silver alloy with high electrochemical potential, biocompatibility, and adjusted degradation behavior is required as an additive for iron-based bioresorbable materials. Several silver alloying systems are possible, but regarding the electrochemical potential and degradation behavior of binary alloys, calcium (Ca) and lanthanum (La) are best-suited considering their biocompatibility. Accordingly, this research addresses AgCa and AgCaLa alloys as additives for iron-based degradable materials with adapted degradation behavior.

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Time efficient laser modification of steel surfaces for advanced bonding in hybrid materials - Voswinkel, Dietrich; Kloidt, D.; Grydin, Olexandr; Schaper, Mirko (Production Engineering)
Abstract Laser surface treatment of metals is one option to improve their properties for adhesive bonding. In this paper, a pulsed YVO4 Laser source with a wavelength of 1064 nm and a maximum power of 25 W was utilized to increase the surface area of the steel HCT490X in order to improve its bonding properties with a carbon fibre reinforced polymer (CFRP). Investigated was the influence of the scanning speed of the laser source on the bonding properties. For this purpose, the steel surfaces were ablated at a scanning speed between 1500 and 4500 mm/s. Afterwards the components were bonded with the adhesive HexBond™ 677. After lap shear tests were carried out on the specimen, the surfaces were inspected using scanning electron microscopy (SEM). The experiments revealed that the bonding quality can be improved with a high scanning speed, even when the surface is not completely ablated.

Zinc Anodizing: Structural Diversity of Anodic Zinc Oxide Controlled by the Type of Electrolyte - Engelkemeier, Katja; Sun, Aijia; Voswinkel, Dietrich; Grydin, Olexandr; Schaper, Mirko; Bremser, Wolfgang (ChemElectroChem)

Laser beam melting of functionally graded materials with application-adapted tailoring of magnetic and mechanical performance - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)

Quasi in-situ analysis of fracture path during cyclic loading of double-edged U notched additively manufactured FeCo alloy - Pramanik, Sudipta; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (International Journal of Fatigue)

Investigating the microstructure of an additively manufactured FeCo alloy: an electron microscopy study - Pramanik, Sudipta; Tasche, Lennart; Hoyer, Kay-Peter; Schaper, Mirko (Additive Manufacturing)

Characterization of phase transformations during graded thermo- mechanical treatment of steel 22MnB5 by means of optical methods - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Materials Data for Smart Forming Technologies)

Plattdeutsch im Kreis Höxter. "Der Dialektatlas Mittleres Westdeutschland (DMW)" und die Frage "Wie klingt Plattdeutsch im Kreis Höxter?" - Wallmeier, Nadine (Kreis Höxter Jahrbuch)

Das paderbörnische Platt. Niederdeutsch im Gebiet der Kreise Paderborn und Höxter - Tophinke, Doris; Wallmeier, Nadine; Merten, Marie-Luis

Theoriekonformität von Unterrichtsplanungen im Fach Physik vor und nach dem Praxissemester - Mutschler, Tanja; Buschhüter, David; Schröder, Jan; Riese, Josef; Borowski, Andreas (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020)

Erwerb physikdidaktischen Wissens zum Einsatz digitaler Medien im Physikunterricht - Große-Heilmann, Rike Isabel; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Längsschnitt Physikdidaktischen Wissens: Ursachen für Veränderungen - Joswig-Käfer, Ann-Kathrin; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Praktische technische Kompetenzen im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Digitale Kompetenzen im Techniklehramt - Albert, Gerrit; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Entwicklung der Fähigkeit zur Unterrichtsplanung im Fach Physik - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020)

Service life estimation of self‐piercing riveted joints by linear damage accumulation - Masendorf, Lukas; Wächter, Michael; Esderts, Alfons; Otroshi, Mortaza; Meschut, Gerson (Fatigue & Fracture of Engineering Materials & Structures)

Correlation bound for a one-dimensional continuous long-range Ising model - Hasler, David; Hinrichs, Benjamin; Siebert, Oliver (Stochastic Processes and their Applications)
We consider a measure given as the continuum limit of a one-dimensional Ising model with long-range translationally invariant interactions. Mathematically, the measure can be described by a self-interacting Poisson driven jump process. We prove a correlation inequality, estimating the magnetic susceptibility of this model, which holds for small norm of the interaction function. The bound on the magnetic susceptibility has applications in quantum field theory and can be used to prove existence of ground states for the spin boson model.

Into the Woods: Experiences from Building a Dataflow Analysis Framework for C/C++ - Schubert, Philipp; Hermann, Ben; Bodden, Eric; Leer, Richard (SCAM '21: IEEE International Working Conference on Source Code Analysis and Manipulation (Engineering Track))

Modeling the Effects of Global Variables in Data-Flow Analysis for C/C++ - Schubert, Philipp; Sattler, Florian; Schiebel, Fabian; Hermann, Ben; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

High Modulation Efficiency Segmented Mach-Zehnder Modulator Monolithically Integrated with Linear Driver in 0.25 \textmum BiCMOS Technology - Kress, Christian; Singh, Karanveer; Schwabe, Tobias; Preußler, Stefan; Schneider, Thomas; Scheytt, J. Christoph (OSA Advanced Photonics Congress 2021)
We present a monolithically integrated electronic-photonic Mach-Zehnder modulator with a linear, segmented driver on the same silicon substrate. As metric for the modulation efficiency, the external V$π$ is hereby reduced to only 420 mV.
Keywords: Analog to digital converters; Extinction ratios; Grating couplers; Modulation; Modulators; Phase shift

Analysis of the effects of jitter, relative intensity noise, and nonlinearity on a photonic digital-to-analog converter based on optical Nyquist pulse synthesis - Kress, Christian; Bahmanian, Meysam; Schwabe, Tobias; Scheytt, J. Christoph (Opt. Express)
An analysis of an optical Nyquist pulse synthesizer using Mach-Zehnder modulators is presented. The analysis allows to predict the upper limit of the effective number of bits of this type of photonic digital-to-analog converter. The analytical solution has been verified by means of electro-optic simulations. With this analysis the limiting factor for certain scenarios: relative intensity noise, distortions by driving the Mach-Zehnder modulator, or the signal generator phase noise can quickly be identified.
Keywords: Analog to digital converters; Diode lasers; Laser sources; Phase noise; Signal processing; Wavelength division multiplexers

Governance and Reputation in the Market for Experience Goods - Fanasch, Patrizia

Conceptualising and measuring domain-specific content knowledge of early childhood educators: A systematic review - Bruns, Julia; Gasteiger, Hedwig; Strahl, Carolin (Review of Education)
The role of domain-specific content knowledge is discussed controversially for the early childhood context. Therefore, this review aims at untangling the research on domain-specific content knowledge for early childhood educators by systematically reviewing the conceptual and operational definition of and results on early childhood educators' content knowledge in different domains. Using the scientific databases ERIC, PsycInfo and Web of Sciences, we identified 36 studies on early childhood educators' domain-specific content knowledge. By comparing these studies, we found that conceptualizations of early childhood educators' content knowledge move on a continuum between a scientific related perspective and a practice related perspective. The scientific related perspective defines content knowledge as the knowledge of key concepts, facts and rules of the domain integrating knowledge taught in primary, secondary or upper secondary school. The practice related perspective includes knowledge of key concepts, facts and rules of the domain limited to the knowledge explicitly relevant for teaching in early childhood education as well as selected domain-specific knowledge of children and teaching. Our review shows that the results and implications drawn by the study authors depend on how these authors conceptualize early childhood educators' content knowledge on this continuum. Further research, therefore, needs to consider carefully how early childhood educators' content knowledge is conceptualized. The paper further discusses gaps in this research field, such as validating methods for measuring early childhood educators' content knowledge or implementing more rigorous experimental designs to examine effects of early childhood educators' content knowledge.
Keywords: content knowledge; domain-specific learning; early childhood education; teacher knowledge

Eine mustergültige Wissenschaft - Bruns, Julia; Schopferer, T. (. TPS – Theorie und Praxis der Sozialpädagogik)

Place value and regrouping as seperate constructs of place value understanding - Jensen, Solveig; Gasteiger, Hedwig; Bruns, Julia (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Context and Implications Document for: Conceptualising and measuring domain-specific content knowledge of early childhood educators: A systematic review - Bruns, Julia; Gasteiger, Hedwig; Strahl, Carolin (Review of Education)

Stellenwertverständnis: Verständnis von Stellenwertprinzip und Bündelungsprinzip als separate Konstrukte - Jensen, Solveig; Gasteiger, Hedwig; Bruns, Julia (Beiträge zum Mathematikunterricht 2021)

The role of strategy-based motivation in mathematical problem solving: The case of learner-generated drawings - Schönherr, Johanna; Schukajlow, S.; Blomberg, J.; Leopold, C. (Learning and Instruction)

inklud.nrw – eine fallbasierte Lehr-/Lernumgebung zum Erwerb inklusions- und digitalisierungsbezogener Kompetenzen in der Lehrer:innenbildung - Herding, Jana; Büker, P.; Kamin, A.M.; Glawe, K.; Oevel, Gudrun; Knurr, M.; Menke, I.; Ogrodowski, J.; Schaper, F. (Bildung in der digitalen Transformation)

Mit Kindern den Übergang auf die weiterführende Schule reflektieren – Sichtweisen von Viertklässler*innen auf die selektiven Schulstrukturen - Herding, Jana; Ogrodowski, J. (Mythen, Widersprüche und Gewissheiten der Grundschulforschung. Eine wissenschaftliche Bestandsaufnahme nach 100 Jahren Grundschule. Jahrbuch Grundschulforschung)

Paderborner Qualitätsstern (PQ³) zur Einschätzung der Kooperation im Übergang Kita – Grundschule: ein Selbstevaluationsinstrument für multiprofessionelle und institutionsübergreifende Zusammenarbeit - Herding, Jana; Höke, J.; Büker, P.; Ogrodowski, J. (Diskurs Kindheits- und Jugendforschung/Discourse. Journal of Childhood and Adolescence Research)

Paderborner Qualitätsstern (PQ³): Self-evaluation of transition to school programms for educators and teachers - Herding, Jana; Büker, P.; Höke, J.; Ogrodowski, J. (Evaluation Transition to School Programms: Learning from Research and Practice)